Relationship between organizational commitment and organizational silence: A study in the insurance industry - Vardarlıer, Pelin; Akıner, Özge (Springer, 2020)
In the study, it was aimed to determine the effect of organizational commitment on organizational silence. In this context, the related research was conducted on 416 employees working in an insurance sector company in Istanbul. In the study, after the concepts of organizational commitment and organizational silence are presented in a theoretical framework, to measure organizational commitment; the scale of organizational commitment by Meyer and Allen, which Wasti and Can translated into Turkish and adapted, and the organizational silence scale developed by Dyne et al. (Journal of Management Studies 40(6), 1359–1392) was used to measure organizational silence. As a result of the questionnaires, the data were evaluated and the relationship between organizational commitment and organizational silence was tried to be explained. The results of multiple regression analysis, which measures the effect of organizational commitment on organizational silence, were interpreted by correlation analysis, which measures the relationships of organizational commitment and organizational silence subdimensions. The results of the T-tests and ANOVA (F) tests, which measure the relationship between demographic variables and research variables, are also included. As a result of the analyzes, it was found that among the subdimensions of organizational commitment, continuing commitment, normative and emotional commitment, only continuing commitment and emotional commitment had a significant effect on accepting silence.
Keywords: Organizational Commitment; Organizational Silence; Insurance Industry